Disparities in veterinary education: a survey comparing first-generation and continuing-generation students in Germany - Kracht, Alexandra Gloria; Doherr, Marcus Georg; Jensen, Katharina Charlotte (Frontiers in Veterinary Science, 2025)
IntroductionAlthough university education in Germany is without tuition fees, the parental educational background influences the decision to study as well as the choice of subjects, and is linked to challenges that students face during the course of study. However, little is known about these aspects in veterinary medicine. In this study, the differences between the first-generation students (FGS) and continuing-generation students (CGS) in veterinary medicine, as well as the challenges (study entrance, financial situation, concerns about the future), are examined in order to identify any need for supportive action.MethodsThe results of this study are based on a survey that was open to all German veterinary students in Spring 2023.ResultsResponses from 1,525 students were analyzed (response rate 24%). A considerable proportion of veterinary students (40%) in Germany are FGS. They are more likely to rate their financial situation as poor (20%) or very poor (7%) than CGS (poor: 10%, very poor: 3%). Even though FGS and CGS work for income alongside their studies in similar proportions (FGS: 71%; CGS: 67%), the motivation was different: CGS are more likely to work in order to earn extra money (CGS: 68%; FGS: 49%) and FGS because other sources of income are insufficient (FGS: 34%; CGS: 12%). A similar proportion of FGS and CGS frequently or consistently considers dropping out of university (FGS: 10%; CGS: 11%). However, in FSG this is more often due to financial reasons (FGS: 28%, CGS: 16%). Almost all students have a high school-based university entrance qualification (97%). Final school grades of CGS were better on average than those of FGS. More FGS than CGS had already completed vocational training prior to their studies (FGS: 47%, CGS: 30%).DiscussionIn conclusion, FGS and CGS differ in their own educational background and the financial challenges in veterinary education. It is therefore important to create an awareness of challenges related to the social background of veterinary students. Moreover, support services to counteract challenges of FGS (and CGS) are needed. There is a need for further research concerning the associations between parental educational background and academic and professional success in veterinary medicine.